Usborne Phonics Readers : Croc Gets a Shock - Mairi Mackinnon (London, United Kingdom Usborne Publishing Ltd, 2013)
Croc is late for everything, even her own birthday party. She misses the bus, she can't buy new shoes because the store is closed for lunch, and what's worse, she has the hiccups. A surprise birthday present may be just what she needs. Simple, phonically repetitive text is a great way to develop essential language and early reading skills, and guidance notes are included to give parents confidence as they help their child learn to read.
Keywords: PY - Language